2014
DOI: 10.1021/es5046309
|View full text |Cite
|
Sign up to set email alerts
|

New Application of Z-Scheme Ag3PO4/g-C3N4Composite in Converting CO2to Fuel

Abstract: This research was designed for the first time to investigate the activities of photocatalytic composite, Ag3PO4/g-C3N4, in converting CO2 to fuels under simulated sunlight irradiation. The composite was synthesized using a simple in situ deposition method and characterized by various techniques including Brunauer-Emmett-Teller method (BET), X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR), scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray photoelectron sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
286
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 838 publications
(306 citation statements)
references
References 65 publications
10
286
0
2
Order By: Relevance
“…In recent years, the g-C 3 N 4 nanostructured materials have been studied for CO 2 photoreduction [92,165], due to their excellent stability, sufficiently negative CB energy and narrow band gap. Many strategies are reported to promote g-C 3 N 4 with condensed matter and molecular sensitizers [166,167], such as doping with metals [168,169] and non-metal [170][171][172], heterojunction construction [173][174][175][176] and Z-scheme composites employing co-catalysts [165][166][167]173,175]. Pengfei et al reported ultrathin C 3 N 4 nanosheets for enhanced photocatalytic CO 2 reduction [177] in which surface functionalization and textural modification by NH 3 -mediated thermal exfoliation enhanced light harvesting, charge-carrier redox potentials, and the surface area for CO 2 adsorption (to 0.2 mmol·g −1 ), resulting in CH 4 and CH 3 OH productivities of 1.39 and 1.87 µmol·h −1 ·g −1 respectively, a five-fold increase over bulk g-C 3 N 4 .…”
Section: Co2 Reductionmentioning
confidence: 99%
“…In recent years, the g-C 3 N 4 nanostructured materials have been studied for CO 2 photoreduction [92,165], due to their excellent stability, sufficiently negative CB energy and narrow band gap. Many strategies are reported to promote g-C 3 N 4 with condensed matter and molecular sensitizers [166,167], such as doping with metals [168,169] and non-metal [170][171][172], heterojunction construction [173][174][175][176] and Z-scheme composites employing co-catalysts [165][166][167]173,175]. Pengfei et al reported ultrathin C 3 N 4 nanosheets for enhanced photocatalytic CO 2 reduction [177] in which surface functionalization and textural modification by NH 3 -mediated thermal exfoliation enhanced light harvesting, charge-carrier redox potentials, and the surface area for CO 2 adsorption (to 0.2 mmol·g −1 ), resulting in CH 4 and CH 3 OH productivities of 1.39 and 1.87 µmol·h −1 ·g −1 respectively, a five-fold increase over bulk g-C 3 N 4 .…”
Section: Co2 Reductionmentioning
confidence: 99%
“…He and co-workers have investigated the activities of photocatalytic composite, Ag 3 PO 4 /g-C 3 N 4 , in converting CO 2 to fuels under simulated sunlight irradiation, where the optimal Ag 3 PO 4 /g-C 3 N 4 photocatalyst shows a CO 2 conversion rate of 57.5 mol h −1 g cat −1 , 6.1 and 10.4 times higher than those of g-C 3 N 4 and P25, respectively [79]. It is proposed that the introduction of Ag 3 PO 4 on g-C 3 N 4 has promoted its light absorption performance.…”
Section: Semiconductor Combinationmentioning
confidence: 99%
“…[70] One more example is the TiO 2 /ZnO composites, which are used to photoreduce CO 2 into CH 4 . [82] Since the finding that photocatalytic water splitting could be realized over the metal-free polymeric g-C 3 N 4 was published in 2009, [83] g-C 3 N 4 has attracted great attention as it is almost ideal for the construction of low-cost photocatalysts such as heterostructured catalysts by coupling with other semiconductors like In 2 O 3 , [84] NaNbO 3 , [67] Ag 3 PO 4 , [85] WO 3 , [53] and ZnO. [86] Obviously, the resultant heterostructured photocatalysts exhibit higher catalytic activity than those of the individual components due to effective charge separation/transfer and prolonged lifetime of the photogenerated charge carriers.…”
Section: Non-p-n Semiconductor Heterostructurementioning
confidence: 99%